2021
DOI: 10.1021/acs.jpca.1c05950
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Mechanism and Products of CO2 Capture by Amines in the Presence of H2O

Abstract: An extensive correlated molecular orbital theory study of the reactions of CO2 with a range of substituted amines and H2O in the gas phase and aqueous solution was performed at the G3­(MP2) level with a self-consistent reaction field approach. The G3­(MP2) calculations were benchmarked at the CCSD­(T)/CBS level for NH3 reactions. A catalytic NH3 reduces the energy barrier more than a catalytic H2O for the formation of H2NCOOH and H2CO3. In aqueous solution, the barriers to form both H2NCOOH and H2CO3 are reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…The advance in spectroscopy, in situ techniques, and quantum mechanical modeling in the past decade promoted mechanistic investigations to unveil the underlying mechanism of CO 2 adsorption and desorption. Commonly used techniques in this field are infrared spectroscopy, , nuclear magnetic resonance (NMR), and density functional theory (DFT). , This chapter briefly summarizes what information can be gained by each technique and major findings related to CO 2 adsorption mechanisms.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The advance in spectroscopy, in situ techniques, and quantum mechanical modeling in the past decade promoted mechanistic investigations to unveil the underlying mechanism of CO 2 adsorption and desorption. Commonly used techniques in this field are infrared spectroscopy, , nuclear magnetic resonance (NMR), and density functional theory (DFT). , This chapter briefly summarizes what information can be gained by each technique and major findings related to CO 2 adsorption mechanisms.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…DFT calculations contributed considerably to understanding what species is favorably formed and what reaction path is reasonable for the reaction of amines with CO 2 . , Early stage research was reported by Mebane et al that the formation of a zwitterion was unstable in a polar environment of anhydrous PEI . However, a dielectric medium under humid conditions stabilizes the zwitterion.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…20 Carbamic acid formation can be catalyzed by H 2 O, decreasing the enthalpy barrier by 30 kcal/mol and the free energy barrier by 12 kcal/mol. 20 The catalytic effect of H 2 O on cyclic carbamic acid derivatives will be explored in future work.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…The mechanisms for the capture and conversion of CO 2 with a range of substituted amines in the gas phase and in aqueous systems has been studied using correlated molecular orbital theory with the results compared to experiment and to other computational studies. 20 Incorporation of nitrogen into 3-and 4-membered rings, forming nitrogen heterocycles, changes the method of gas capture compared to standard amines. The ability of such Nheterocycles to trap acid gases, primarily CO 2 , has been demonstrated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have indicated that H 2 O affects the adsorption of CO 2 , but the presence of CO 2 does not significantly affect the adsorption of H 2 O. 112,278,400,563 While several studies on the development of new adsorbent materials have explored their adsorption properties in the presence of H 2 O, little is known about the detailed mechanism of the interaction between H 2 O and CO 2 .…”
Section: Cooperative Adsorption Of H 2 O and Comentioning
confidence: 99%